ESTIMATION OF ARTHROPODS DISTRIBUTIONAL PATTERN OCCURS WITH RESPECT TO SPATIOTEMPORAL FACTOR IN CITRUS ORCHARDS OF DIFFERENT LANDSCAPES - Waqar Majeed; Naureen Rana; Nazia Ehsan (Journal of Animal and Plant Sciences, 2026)
Decisions on land management and conservation should consider how the taxonomic and functional diversity of animal species react to land management in various locations. This study examined arthropod species diversity over space and time in four different regions (Faisalabad, Layyah, Vehari and Sahiwal) of Punjab, Pakistan. We sampled the arthropod fauna fortnightly for two years, January 2020- December 2021. A total of 16794 specimens were collected from all the sites. The highest abundance was found from Faisalabad 32.99% (n = 5542), followed by Sahiwal 26.01% (n = 4369), Vehari 23.73% (n = 3986) and the least was recorded from Layyah 17.25% (n = 2897). Diversity and abundance were greatest in Faisalabad and lowest in Layyah, while Vehari and Sahiwal had nearly similar diversity, likely because of similar environmental conditions. The highest abundance was recorded from Faisalabad orchards for Diaphorina citri Kuwayama, 1908 (Liviidae: Hemiptera) 5.88% (n=326), Layyah: Coccinella septempunctata Linnaeus, 1758 (Coccinellidae: Coleoptera) 3.97% (n=115), Vehari: Culex quinquefasciatus Say, 1823 (Culicidae: Diptera) 4.11% (n=164), Sahiwal: Bactrocera dorsalis Hendel, 1912 (Tephritidae: Diptera) 4.44% (n=194). Diversity (H) was recorded from Faisalabad 4.52 and Evenness was maximum in Layyah 0.813. Species diversity and abundance in Layyah are likely mainly affected by severe weather with fluctuating temperatures and humidity. The species richness varied along the latitudinal gradient and lower abundance was found at higher latitudes. A non-metric multidimensional scaling (NMDS) ordination showed clear clusters of regional assemblages that varied along a clear gradient. This research will assist future management and conservation of arthropods in Pakistan by providing a baseline for the diversity and abundance.
Keywords: Abundance; Arthropods; Diversity; Ecological community; Richness